Improvement in endothelial function in cardiovascular disease - Is arginase the target?. (15th February 2020) - Mahdi, Ali; Kövamees, Oskar; Pernow, John
Abstract: Endothelial dysfunction represents an early change in the vascular wall in areas prone to atherosclerotic plaque formation and is present in association with several risk factors for cardiovascular disease. The underlying mechanisms behind endothelial dysfunction are multifactorial and complex. Arginase has emerged as a key player in the regulation of endothelial integrity by the ability of reciprocally inhibits nitric oxide formation and promoting oxidative stress. A chain of evidence suggest that arginase is implicated in the pathogenesis underlying endothelial dysfunction induced by several cardiovascular risk factors and established cardiovascular disease including diabetes, hypercholesteremia, ischemia/reperfusion, atherosclerosis, obesity, ageing and hypertension. Recent data has unveiled a key role of arginase as one of the key mechanisms underlying endothelial dysfunction in diabetes and may serve as a potential therapeutic target in previously overlooked compartments including red blood cells. The current review is devoted to discuss arginase as a key mediator in endothelial dysfunction and the potential for therapeutic possibilities to target this enzyme in various diseases, especially type 2 diabetes, atherosclerosis and ischemia/reperfusion with focus on translational and clinical aspects. Moreover, approaches of how and in which patient group(s) arginase may be targeted in future clinical trials are discussed. Graphical abstract: Unlabelled Image Highlights: Endothelial dysfunction represents the earliest detectable change in the development of atherosclerotic lesions. Arginase is a key factor in endothelial dysfunction by reducing nitric oxide bioavailability and increasing oxidative stress. Upregulated arginase activity is a pathophysiological factor in several cardiovascular diseases. Arginase is a potential effective therapeutic target in cardiovascular disease.